Pengaruh Asupan Gizi Terhadap Tingkat Kecerdasan Linguistik dan Intrapersonal Anak di RA Kafala Mergosari Tarik Sidoarjo - Nitami, Titak; Al Mubarok, Ahmad Aly Syukron Aziz (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2023)
Nutritional intake for early childhood is very important because it affects the process of growth and development until they are in adulthood, the benefits of nutritional intake for early childhood include maintaining health, increasing therefore, the fulfillment of the best nutritional intake will affect children's learning achievement at school. This type of research is quantitative-associative, with data collection techniques using observation and documentation, while data analysis techniques using Computer Program techniques, namely SPSS Version 25 for windows. There is a significant positive effect with a low degree of nutritional intake on the level of linguistic intelligence in RA Kapala Mergosari Tarik Sidoarjo. This is evident from the results of empirical research finding that the influence of learning aqidah morals on assertive behavior in Tables 4.23 and Tables 4.24 can be explained that the value of the correlation coefficient (rxy) between nutritional intake and the level of linguistic intelligence is 0.646 and Fcount (F Change) = 27.282 and Ftable = 4.05 with p-value = 0.000 <0.05. This Ha is accepted or proven true, while the null hypothesis (H0) is rejected. The magnitude of the coefficient of determination (R Square) is 0.646. There is a positive influence of nutritional intake on intrapersonal intelligence in RA Kafala Mergosari Tarik Sidoarjo. One of the factors that influence children's intrapersonal intelligence is nutritional intake consumed through daily food. Based on table 4.27 and table 4.28 it can be explained that the value of the correlation coefficient ( rxy) between nutritional intake on intrapersonal intelligence 0.658 and Fcount (F Change) = 28, 924 and Ftable = 4.05 with p-value = 0.002 <0.05. Thus, the effect of nutritional intake on intrapersonal intelligence is significant.